KEYNOTE The Unravelling Patriarchy - Tronto, Joan (feminists@law, 2018)
This is a video of Joan Tronto's Keynote address at the Sexual Contract: 30 Years On conference held at the School of Law and Politics, Cardiff University on 10-11 May 2018. In her address, Tronto begins with Carole Pateman's insight in The Sexual Contract (1988) about the incapacity of contract to produce freedom and equality, and considers the possibilities for an alternative organisation of human relations based on care ethics. She observes that in the years since the publication of The Sexual Contract, neoliberalism has resulted in a rewriting of the sexual contract. Under neoliberalism, the entry of women into the labour market, the full commodification of women's work and increasing economic disparities between men have resulted in some women becoming 'honorary individuals', substantially autonomous of men, with the consequent disruption of both men's political and sexual domination of women. This process has, in turn, given rise to a violent, misogynist and antidemocratic backlash in the form of neopopulism, in which men who have lost out economically feel a sense of deprivation, blame women, and seek a return to earlier forms of patriarchal domination. Against this background, she argues, care ethics provides a means of rethinking democratic commitments. A more just allocation of caring responsibilities could lead to a caring democracy without a return to gender subordination.